Formulasi Sediaan Sabun Cair Cuci Tangan Kombinasi Minyak Atsiri Daun Kemangi dan Minyak Atsiri Sereh Wangi serta Uji Aktivitas Antibakteri - Dasmyta, Eny; Anwar, Yelfi; Maryana, Roni; Muryanto, Muryanto (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Liquid hand soap is a cleaning product specifically designed to clean hands from dirt, oil, and microorganisms. The study aims to provide evidence of antibacterial efficacy with a combination of basil leaf essential oil and citronella essential oil on Escherichia coli and Staphylococcus aureus bacteria in hand washing liquid soap formulations. The type of research used is experimental. Essential oils were analyzed by GC-MS and then through formulation as hand washing liquid soap with each concentration of 1%, 1.5%, and 2%. The test results were evaluated, and analyzed using Two Way ANOVA and Post Hoc Tukey.The results of this study showed that the GC-MS test on basil leaf essential oil showed 2 main compounds were detected, namely Estragole (55.80%) and Linalool (22.35%), while in citronella essential oil 3 main compounds were detected, namely Geraniol (26.49%), Citronellol (14.53%), and Citronellal (10.95%). And the results of antibacterial activity tests against Escherichia coli bacteria show each inhibition zone FI 9.32 mm, FII 10.72 mm, and FIII 14.45 mm. While against Staphylococcus aureus bacteria showed each inhibition zone FI 8.75 mm, FII 10.42 mm, and FIII 13.57 mm. For stability tests with temperature (2-8oC) and room temperature (20-25oC), the hand washing liquid soap formulation does not show homogeneous changes, organoleptic preparations, has a pH range of 8.87 - 9.04, has a viscosity consistency that has met the standards between 400-4000 cPs, foam height that meets the standards between 13-220 mm and does not cause irritation to the hands. In brief, the formulation is stable in both temperature (2-8oC) and room temperature (20-25oC) with strong inhibition at 2% concentration.